Tratamento da síndrome do túnel do carpo com laser - Monteiro, Tamiris Aparecida [UNESP] (2015)
The carpal tunnel syndrome (CTS) is the most common entrapment neuropathy. After surgery different types of complication may occur, than search for new clinical forms of treatment is necessary. The aim of this study was to test the effectiveness of low intensity laser therapy in patients with CTS. Patients with clinical and ENMG diagnosis of CTS never previously treated were included and submitted to clinical evaluation and conduction studies before and after treatment. Sensory and motor conduction studies were performed by conventional described techniques. Low intensity laser treatment was by 660 nm wave length, average power of 30 nw, continuous operation area of 0.06 cm2, fluence of irradiation of 10 J/cm2, exposure of 10 seconds per point, totaling 6 points of irradiation on the carpal tunnel, from the proximal to the distal sense. Laser was positioned at 90o to the skin, 2 sessions per week during 3 months were performed (24 sessions). To this moment 20 hands of 13 patients were studied. Visual analogic scale of pain (VAS), strength of the abductor pollicis brevis and sensory velocity of the median nerve showed improvement after the treatment (p < 0.0001, 0.0003 and 0.045, respectively). No correlation between these 3 parameters were observed from the Spearman correlation test. In our opinion low intensity laser therapy is a new, no expensive and easy to apply encouraging treatment for CTS